THE RELATIONSHIP OF HUSBAND SUPPORT WITH EXCLUSIVE BREAST FEEDING - Puspita Maulina; Juli Oktalia; Willa Follona (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
Background: Breastfeeding is not a completely instinctive behavior, and theoretical breastfeeding guidance is not enough, but supportive assistance from health workers, husbands and families is also needed. A mother needs a practitioner's help to confirm the latch position, interpret her baby's behavior and respond to it. Mothers need someone who provides support and confidence, namely husband, successful breastfeeding is a joint effort that requires correct information and strong support to create an environment that allows mothers to breastfeed optimally. Objective: This study aims to determine the relationship of husband's support to exclusive breastfeeding at PMB Enok Siti Mampang Depok. Methods: This study is a quantitative study with a cross sectional design, using primary data with a sample of 147 breastfeeding mothers who have babies aged 6-24 months. Results: Based on the results of data analysis using the chi-square test with a significance level or p-value <0.05, it can be concluded that there is a significant relationship between informative, emotional, instrumental support and husband's assessment of exclusive breastfeeding at PMB Enok Siti in 2022. : More and more lactation education not only for mothers but husbands and all the support systems involved. Preparation for breastfeeding should be done prenatally with a partner. And more and more health workers are providing practical assistance to breastfeeding mothers.